The awareness level of the safety and health of the operational level / Roshanira Che Mohd Nor and Nur Atiqah Rochin Demong - Che Mohd Nor, Roshanira; Rochin Demong, Nur Atiqah (Faculty of Business and Management and UiTM Press, Universiti Teknologi MARA, Malaysia, 2017)
Providing a safe and healthy workplace is one of the most effective strategies in for holding down the cost of doing construction business. It was a part of the overall management system to facilitate the management of the occupational health and safety risk that are associated with the business of the organization. Factors affected the awareness level inclusive of safety and health conditions, dangerous working area, long wait care and services and lack of emergency communication were the contributed factors to the awareness level for the operational level. Total of 122 incidents happened at Telekom Malaysia Berhad as compared to year 2015 only 86 cases. Thus, the main objective of this study was to determine the relationship between safety and health factors and the awareness level among operational workers. The determination of this research was to increase the awareness level among the operational level workers who committing to safety and health environment.